2017
DOI: 10.1109/tac.2017.2701005
|View full text |Cite
|
Sign up to set email alerts
|

Event-Triggered State Estimation: An Iterative Algorithm and Optimality Properties

Abstract: This paper investigates the optimal design of event-triggered estimation for linear systems. The synthesis approach is posed as a team decision problem where the decision makers are given by the event-trigger and the estimator. The event-trigger decides upon its available measurements whether the estimator shall obtain the current state information by transmitting it through a resource constrained channel. The objective is to find the optimal trade-off between the mean square estimation error and the expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
0
41
1
Order By: Relevance
“…Several variations of the above model have been considered in the literature. Models with noiseless communication channels have been considered in [1]- [6]. Since the channel is noiseless, these papers assume that there are only two power levels: power level 0, which corresponds to not transmitting; and power level 1, which corresponds to transmitting.…”
Section: A Motivation and Literature Overviewmentioning
confidence: 99%
“…Several variations of the above model have been considered in the literature. Models with noiseless communication channels have been considered in [1]- [6]. Since the channel is noiseless, these papers assume that there are only two power levels: power level 0, which corresponds to not transmitting; and power level 1, which corresponds to transmitting.…”
Section: A Motivation and Literature Overviewmentioning
confidence: 99%
“…The causal sampling and estimation policies that achieve the optimal tradeoff between the sampling frequency and the distortion have been studied for the following discrete-time processes: the i.i.d process [1]; the Gauss-Markov process [2]; the partially observed Gauss-Markov process [3]; and, the first-order autoregressive Markov process X t+1 = aX t + V t driven by an i.i.d. process {V t } with unimodal and even distribution [4] [5]. The first-order autoregressive Markov process considered in [4][5] represents a discrete-time counterpart of the continuous-time process in (5) with q(t, s) = a t−s , R(t, s, τ ) = X t − a t−s X s .…”
Section: Related Work Includes [1]mentioning
confidence: 99%
“…The causal sampling and estimation policies that achieve the optimal tradeoff between the sampling frequency and the distortion have been studied for the following discrete-time processes: the i.i.d process [1]; the Gauss-Markov process [2]; the partially observed Gauss-Markov process [3]; and, the first-order autoregressive Markov process X t+1 = aX t + V t driven by an i.i.d. process {V t } with unimodal and even distribution [4] [5]. The first-order autoregressive Markov process considered in [4][5] represents a discrete-time counterpart of the continuous-time process in (5) with q(t, s) = a t−s , R(t, s, τ ) = X t − a t−s X s .…”
Section: Related Work Includes [1]mentioning
confidence: 99%
“…process {V t } with unimodal and even distribution [4] [5]. The first-order autoregressive Markov process considered in [4][5] represents a discrete-time counterpart of the continuous-time process in (5) with q(t, s) = a t−s , R(t, s, τ ) = X t − a t−s X s . Chakravorty and Mahajan [4] showed that a threshold sampling policy with two constant thresholds and an innovation-based filter jointly minimize a discounted cost function consisting of the MSE and a transmission cost in the infinite time horizon.…”
Section: Related Work Includes [1]mentioning
confidence: 99%